Assessment of Drinking Water Quality in Urban Water Supply Systems: The Case of Hawassa City, Ethiopia - Yirged Antehun Mengstie; Wendesen Mekonin Desta; Esayas Alemayehu (International Journal of Analytical Chemistry)
In many developing countries, such as Ethiopia, water quality and the risk of water-related diseases are serious public health issues. The present study goal was to assess the drinking water quality from source to household tap water. To characterize and analyze drinking water quality parameters, 21 water samples were collected, of which 11 water samples were collected from sources (spring, borehole, and river), 4 from service reservoirs, and 6 from tap water. The mean values of the parameters were as follows: total dissolved solids (TDS) (142.79 mg/L), temperature (22.08°C), turbidity (9.49 NTU), electrical conductivity (EC) (250.14°μS/cm), pH (7.45 mg/L), fluoride (1.15 mg/L), nitrate (NO3−) (2.91 mg/L), total hardness (TH) (57.45 mg/L), calcium (41.7 6 mg/l), magnesium (10.74 mg/L), phosphate (0.44 mg/L), sulfate (3.99 mg/L), residual chlorine (1.53 mg/L), alkalinity (196.39 mg/L), and microbiological (total coliform and coliform/CFU) which were the main physiochemical parameters analyzed for the study. The findings revealed that the majority of the water quality parameters tested were within the WHO and National Drinking Water Quality Standards (NDWQS). However, some of the parameters such as temperature, turbidity, fluoride, and residual chlorine did not meet the standards. The mean temperatures at the source, reservoir, and tap water were 22.01°C 22.5°C,and 21.83°C, respectively. Turbidity levels in source samples ranged from 10 to 45 NTU, with a mean of 24.5 NTU, exceeding the WHO’s recommendation of less than 5 NTU. The Boko Alamura well had a high fluoride content (3.9 mg/l), which was above the WHO and NDWQS permissible limits. There was no free residual chlorine in the tap water sample. The results show that the Hawassa drinking water supply did not contain total or fecal coliform in any of the samples tested. The overall WQI for the water source, reservoir, and tap water was also determined to be 89, 71, and 69.7 points, respectively. Therefore, based on the WQI result, Hawassa drinking water quality is good for the source, reservoir, and tap water.